. Significance of Plasma TGF-β1 Level Detection in Patients with T2DM with Heart Failure: Plasma TGF-β1 Level - Sun, Yunjing (Journal of Medical Biochemistry, 2024)
Abstracts: Objective: To examine the significance of plasma Transforming Growth Factor-1/TGF-1 (TGF-1) level testing in patients with Type 2 Diabetes Mellitus (T2DM) and heart failure. Methods: A sample of T2DM patients who were hospitalised for dyspnea between June 2021 and June 2023 were chosen. Based on the convenience sample approach, 150 cases were screened for the study, and 50 healthy non-diabetic people without cardiac problems who completed physical examinations over the same period were included as a control group. All study participants had their serum NT-proBNP and plasma TGF-I levels checked, and the values between the two groups were compared. Then, the patients with T2DM with heart failure were grouped according to whether they were accompanied by heart failure or not and the grading of cardiac function, and then the serum NT-proBNP and plasma TGF-β1 levels were compared between the different groups of patients. The diagnostic value of plasma TGF-β1 in the occurrence of heart failure in patients with T2DM was analysed. Results: There were 54 patients without heart failure and 96 people with heart failure among the 150 T2DM patients. The cut-off point was 44.50 g/L. At this time, the sensitivity and specificity for the diagnosis of concomitant heart failure in T2DM were 79.63% and 52.51%, respectively. 96 individuals with T2DM and heart failure showed greater serum and plasma levels of NT-proBNP and TGF-1 compared to the other two groups (P 0.05). ProBNP levels and plasma TGF-1 levels had a positive and significant relationship (P 0.05). Conclusion: Plasma TGF-1 levels were much higher in T2DM patients than in the general population, and the increase in this index was more pronounced in patients who also had heart failure, which is a diagnostic indicator for T2DM and heart failure.
Keywords: heart failure; NT-proBNP; Type 2 diabetes mellitus; TGF-β1